2007
DOI: 10.1111/j.1741-2358.2007.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bite force and tongue pressure on oro‐pharyngeal residue in the elderly

Abstract: It is suggested that in the elderly tongue pressure contributed to propulsion of the food bolus from oral cavity into the pharynx, and multiple swallowing contributed to the reduction in the amount of pharyngeal residue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 45 publications
2
44
0
3
Order By: Relevance
“…Several reports have established a relationship between tongue pressure and swallowing dysfunction. Tongue pressure has been associated with the presence of oro-pharyngeal residue using videofluoroscopic examination [9]. In a water-swallowing test, tongue pressure was found to be significantly lower in dysphagic patients than in non-dysphagic patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have established a relationship between tongue pressure and swallowing dysfunction. Tongue pressure has been associated with the presence of oro-pharyngeal residue using videofluoroscopic examination [9]. In a water-swallowing test, tongue pressure was found to be significantly lower in dysphagic patients than in non-dysphagic patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…4A). Because tongue pressure is essential for the movement of a food bolus from the oral cavity into the pharynx [20], declines of MTP resulted in increased Ns in all three diseases (Figs. 3G and 4D).…”
Section: Discussionmentioning
confidence: 98%
“…A previous study determined age-related decrease in maximal tongue pressure based on the maximal voluntary isometric contraction measured in Japanese subjects of different age groups [37]. It is also reported that decreased maximal voluntarily isometric contraction in older subjects appears to reflect clinical signs of dysphagia [38]: as high maximal voluntary isometric contraction increases, the food residue observed in the oral cavity shows a decrease after masticating at a certain number of times and swallowing once, in the aged [39]. Following extensive research, this device has been developed for clinical use and is expected to be commercially available in the near future.…”
Section: Sensing Of Tongue Movementmentioning
confidence: 99%